2010
DOI: 10.3389/fpsyt.2010.00134
|View full text |Cite
|
Sign up to set email alerts
|

Inverse effects of oxytocin on attributing mental activity to others in depressed and healthy subjects: a double-blind placebo controlled fMRI study

Abstract: Background: Oxytocin is a stress-attenuating and pro-social neuropeptide. To date, no study has looked at the effects of oxytocin in modulating brain activity in depressed individuals nor attempted to correlate this activity with attribution of mental activity in others. Method: We enrolled 10 unmedicated depressed adults and 10 matched healthy controls in a crossover, double blind placebo controlled fMRI 40 i.u. intra-nasal oxytocin study (20 i.u. per nostril). Each subject performed reading the mind in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 56 publications
3
58
0
Order By: Relevance
“…25 We examined 6 studies addressing the reward system after OXT administration. 23,25,30,32,35,39 We found that OXT administration has an effect over reward-related learning in that it seems to increase activation associated with reward-related learning in the caudate while decreasing learning effects. It has a similar influence on activation in the putamen, but is specific to learning during social interactions.…”
Section: Fmri Studies In Humansmentioning
confidence: 82%
See 4 more Smart Citations
“…25 We examined 6 studies addressing the reward system after OXT administration. 23,25,30,32,35,39 We found that OXT administration has an effect over reward-related learning in that it seems to increase activation associated with reward-related learning in the caudate while decreasing learning effects. It has a similar influence on activation in the putamen, but is specific to learning during social interactions.…”
Section: Fmri Studies In Humansmentioning
confidence: 82%
“…Four studies have addressed the role of the caudate after OXT administration. 23,32,35,39 The correlation between action and outcome in terms of action contingency appears to be activated exclusively within the left caudate, and activation correlates with prediction error during instrumental conditioning. 52,53 On the other hand, bilateral activation of the caudate is observed in games involving trust where increased activity was related to an "intention to trust."…”
Section: Caudatementioning
confidence: 99%
See 3 more Smart Citations